Anomalous Enthalpy Relaxation in Vitreous Silica - Yue, Yuanzheng (Frontiers in Materials, 2015)
It is a challenge to calorimetrically determine the glass transition temperature (Tg) of vitreous silica. Here we demonstrate that this challenge mainly arises from the extreme sensitivity of the Tg to the hydroxyl content in vitreous silica, but also from the irreversibility of its glass transition when repeating the calorimetric scans. It is known that the liquid fragility (i.e., the speed of the viscous slow-down of a supercooled liquid at its Tg during cooling) has impact on enthalpy relaxation in glass. Here we find that vitreous silica (as a strong system) exhibits striking anomalies in both glass transition and enthalpy relaxation compared to fragile oxide systems. The anomalous enthalpy relaxation of vitreous silica is discovered by performing the hperquenching-annealing-calorimetry experiments. We argue that the strong systems like vitreous silica and vitreous Germania relax in a structurally cooperative manner, whereas the fragile ones do in a structurally independent fashion. We discuss the origin of the anomalous enthalpy relaxation in the HQ vitreous silica.